Steroids accumulate in the rearing water of commercial recirculating aquaculture systems - Mota, Vasco (2015)
Little information is available on steroid concentrations in the rearing water of aquaculture systemsand whether they accumulate in recirculating aquaculture systems (RAS). Therefore this study aimedat determining (1) the concentrations and variation of cortisol and sex steroids in RAS, (2) the con-tribution of fish rearing conditions to steroid concentrations in seven commercial RAS. Each RAS wassampled twice at three different points: (1) make-up water; (2) influent and (3) effluent of the rear-ing unit. The results showed significant higher steroid concentrations in the influent and effluent whencompared with the make-up water. On average cortisol concentration was 15.7% higher in the efflu-ent when compared with the influent. Mean steroid concentrations in the rearing unit effluent variedbetween: 3.8–217.0 ng/L for cortisol, 3–12.5 ng/L for testosterone, 0.9–7.1 ng/L for 11-ketoteststerone and1.8–12.8 ng/L for 17,20 -dihydroxypregn-4-en-3-one. Stocking density, Total Ammonia-Nitrogen con-centration and orthophosphate-P concentration (a measure of make-up water usage) showed a positivecorrelation with sex steroids in the water. The steroid concentrations from the present study were ordersof magnitude lower than initial estimations indicating a water treatment efficiency of >99%. The resultssuggest that an intensification of fish production through decrease of make-up water use and increaseof stocking density will lead to a build-up of steroids in the water. Although intensification is critical forthe economical success of RAS, this ultimately could affect fish performance as steroids accumulates inthe water of RAS at levels that can potentially be detected by some fish species.